A deficiency screen identifies genomic regions critical for sperm head-tail connection. - Galletta, B.J.; Konstantinidou, P.; Haase, A.D.; Rusan, N.M. (G3 : genes - genomes - genetics, 2025)
The Sperm Neck provides a stable connection between the sperm head and tail, which is critical for fertility in species with flagellated sperm. Within the Sperm Neck, the Head-Tail Coupling Apparatus serves as the critical link between the nucleus (head) and the axoneme (tail) via the centriole. To identify regions of the Drosophila melanogaster genome that contain genetic elements that influence Head-Tail Coupling Apparatus formation, we undertook a 2 part screen using the Drosophila Deficiency kit. For this screen, we utilized a sensitized genetic background that overexpresses the pericentriolar material regulatory protein Pericentrin-Like Protein. We had previously shown that Pericentrin-Like Protein overexpression disrupts the head-tail connection in some spermatids, but not to a degree sufficient to reduce fertility. In the first step of the screen, we tested for deficiencies that in combination with Pericentrin-Like Protein overexpression causes a reduction in fertility. We ultimately identified 11 regions of the genome that resulted in an enhanced fertility defect when combined with Pericentrin-Like Protein overexpression. In the second step of the screen, we tested these deficiencies for their ability to enhance the head-tail connection defect caused by Pericentrin-Like Protein overexpression, finding 6 genomic regions. We then tested smaller deficiencies to narrow the region of the genome that contained these enhancers and examined the expression patterns of the genes within these deficiencies using publicly available datasets of Drosophila tissue RNAseq and Drosophila testes snRNAseq. In total, our analysis suggests that some deficiencies may contain single genes that influence Head-Tail Coupling Apparatus formation or fertility, while other deficiencies appear to be genomic regions rich in testis-expressed genes that might affect the Head-Tail Coupling Apparatus through complex, multigene interactions.